Weapons of the Weak : Everyday Forms of Peasant Resistance. - Scott, James C. (Yale University Press, 2008)
This sensitive picture of the constant and circumspect struggle waged by peasants materially and ideologically against their oppressors shows that techniques of evasion and resistance may represent the most significant and effective means of class struggle in the long run."A major contribution to peasant studies, Malaysian studies, and the literature on revolutions and class consciousness."--Benedict R. Anderson, Cornell University"The book is a splendid achievement. Because Scott listens closely to the villagers of Malaysia, he enormously expands our understanding of popular ideology and therefore of popular politics. And because he is also a brilliant analyst, he draws upon this concrete experience to develop a new critique of classical theories of ideology."--Frances Fox Piven, Graduate Center of the City University of New York"An impressive work which may well become a classic."--Terence J. Byres, Times Literary Supplement"A highly readable, contextually sensitive, theoretically astute ethnography of a moral system in change ... Weapons of the Weak is a brilliant book, combining a sure feel for the subjective side of struggle with a deft handling of economic and political trends."--John R. Bown, Journal of Peasant Studies"A splendid book, a worthy addition to the classic studies of Malay society and of the peasantry at large ... Combines the readability of Akenfield or Pig Earth with an accessible and illuminating theoretical commentary."--A.F. Robertson, Times Higher Education Supplement"No one who wants to understand peasant society, in or out of Southeast Asia, or theories of change, should fail to read [this book]."--Daniel S. Lev, Journal of Asian Studies"A moving account of the poor's refusal to accept the terms of their subordination ... Disposes of the belief that theoretical sophistication and intelligible prose are somehow at odds."--Ramachandra Guha, Economic and Political Weekly"A seminally important commentary on the state of peasant studies and the global literature ... This enormously rich work in Asian and comparative studies is ... an essential contribution to participatory development theory and practice."--Guy Gran, World DevelopmentJames C. Scott is professor of political science at Yale University.